Foreign Series in the Kurdish Satellite Channels and Their Role in the Development of Awareness among Young People in the Kurdistan Region (Korean Series as a Model) (A Field Study on a Sample of Students of the Institute of Fine Arts in the City of Sulay - Majeed Hassan, Heiman (ALBAHITH ALALAMI, 2013)
The dubbing process for the Foreign Dramas by the Kurdish language became a serious phenomenon in the Kurdish satellite TV, especially in the past few years. It attracted a wide audience, especially young adolescents. And prepared by some breakthrough hostile to Kurdish culture and value coordinated by others remedy for the structural gaps and lapses have, as a result of climate which is brought into existence globalization and secretions variety dimensional, saturated value and cognitive effects bearing a strong identity of its elements. From here, the problem of this research is the ambiguity of their role in a series of developmental processes Kurdish awareness of young people and the extent of the impact that caused it. This research is important from the theme referred to above, which is still an important focus on the priorities of community knowledge, information and technical and popular and others, as well as it studies the few that deal with this kind of soap operas and effects of development on the awareness of the youth, which contributes to the enrichment of Kurdish Library and alert researchers new interesting its other aspects that have not been studied yet. This research as a description example aims to detect and confirm the type and importance of the information and knowledge provided by these serials for various community affairs and how they are displayed and interpreted, and to identify the motives of exposure receiver to those series and duration of time. This research is somewhat descriptive research, which is through the study of the facts associated with the variables in question and clarifies, targeting recognized indicators laxatives to understand its ties with other phenomena. To achieve the objectives of this research, and to invoke the curriculum survey which demonstrated suitability for this purpose as proven by many scientific researches, I realized many important results, including: • The information offered by the Korean series showed by the Kurdish satellite TV in the Kurdistan Region is adequate information and relative value, community events and crises in general. • Sufficiency of those series to provide explanations and public surface phenomena and economic crisis and none sank in detail the structural and influential. • Creating those negative effects series with the relative majority of respondents to the concepts of democracy and public freedoms, taking into consideration the dissenting views that compete with such a majority in number. • The existence of contradictory assertions and relatively neutral, towards a pseudo- interpretation of the Korean Series about the fairness of factional strife in society and immortality. The study, finally, sets some recommendations including: • Follow-up young families for their children, especially adolescents and guiding them towards viewing main dramas. • Kurdish interest in drama and the study develops and supports to bring it to the level of competition with foreign drama through productivity and up-gradation of art and technology.